2000
DOI: 10.1080/001401300404698
|View full text |Cite
|
Sign up to set email alerts
|

Effects of load carriage on heart rate, blood pressure and energy expenditure in children

Abstract: Fifteen male primary school children, aged 10 years, were selected to carry school bags of 10, 15 and 20% of their own body weights, where 0% body weight was used as a control. Maximum oxygen uptake (VO2max) tests were conducted on a motorized treadmill using a continuous incremental protocol. During the load carrying test, subjects walked on a treadmill at 1.1 m s(-1) for 20 min at each load condition. Blood pressures were measured before, immediately following, and at 3 and 5 min after every trial. Heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
55
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 6 publications
5
55
1
3
Order By: Relevance
“…Many researchers found that the average bag weight carried by the school children should not exceed 10% of the body weight 2,3,5,6 . There were 12,688 acute injuries associated with backpacks in the US 7 . The daily changes/adaptions in posture with the varying load may cause pain and musculoskeletal disorders (MSDs) among school children 8,9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers found that the average bag weight carried by the school children should not exceed 10% of the body weight 2,3,5,6 . There were 12,688 acute injuries associated with backpacks in the US 7 . The daily changes/adaptions in posture with the varying load may cause pain and musculoskeletal disorders (MSDs) among school children 8,9 .…”
mentioning
confidence: 99%
“…The study consisted of 60 randomly selected school going male students (20 from each school and 5 from each of class 5,6,7,8). On the basis of questionnaire, only those students who had no history of orthopaedic, neuromuscular or cognitive disorder were selected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Load limit of 10% -15% of Body Weight (BW) among children and adolescents for backpack carriage is acceptable according to physiological data [5,6]. Load carriage has been observed to affect physiological parameters like heart rate, blood pressure and energy expenditure among children [7]. Literature survey revealed that significant amount of work has already been done to show relationship between backpack carriage and lung function parameters among children and adolescents but has not been explicitly studied among young adults [8].…”
Section: Introductionmentioning
confidence: 99%
“…Lung function is related with oxygen uptake and hence with the energy expenditure [7] thus lung function is a vital physiological parameter which governs the cumulative stress on the body. Heavy load placed near trunk affects lung function and reduction in lung function is dependent on the percentage of load.…”
Section: Introductionmentioning
confidence: 99%